HeRAFC: Heuristic resource allocation and optimization in MultiFog-Cloud environment - Dehury, Chinmaya Kumar; Veeravalli, Bharadwaj; Srirama, Satish Narayana (Journal of parallel and distributed computing, 2024)
By bringing computing capacity from a remote cloud environment closer to the user, fog computing is introduced. As a result, users can access the services from more nearby computing environments, resulting in better quality of service and lower latency on the network. From the service providers' point of view, this addresses the network latency and congestion issues. This is achieved by deploying the services in cloud and fog computing environments. The responsibility of service providers is to manage the heterogeneous resources available in both computing environments. In recent years, resource management strategies have made it possible to efficiently allocate resources from nearby fog and clouds to users' applications. Unfortunately, these existing resource management strategies fail to give the desired result when the service providers have the opportunity to allocate the resources to the users' application from fog nodes that are at a multi-hop distance from the nearby fog node. The complexity of this resource management problem drastically increases in a MultiFog-Cloud environment. This problem motivates us to revisit and present a novel Heuristic Resource Allocation and Optimization algorithm in a MultiFog-Cloud (HeRAFC) environment. Taking users' application priority, execution time, and communication latency into account, HeRAFC optimizes resource utilization and minimizes cloud load. The proposed algorithm is evaluated and compared with related algorithms. The simulation results show the efficiency of the proposed HeRAFC over other algorithms. •The resource allocation problem in a multifog-cloud environment is studied.•The physical infrastructure of multifog-cloud is modeled using graph theory.•The resource allocation problem is formulated with a mixed ILP model.•The proposed algorithm can also deploy the user's task on nearby fog nodes.•Simulation results outperform other related algorithms in said environment.